2017
DOI: 10.1038/s41598-017-00861-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interstitial fluid drainage in the hippocampus of spontaneously hypertensive rats

Abstract: Hypertension is associated with cognitive decline and various forms of dementia, including Alzheimer’s disease. In animal models of hypertension, many of Alzheimer’s disease characteristics are recapitulated, including brain atrophy, cognitive decline, amyloid β accumulation and blood brain barrier dysfunction. Removal of amyloid β and other waste products depends in part on clearance via the brain interstitial fluid (ISF). Here we studied the impact of hypertension on ISF drainage, using spontaneously hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…15,16 Therefore, hippocampal Amh has the potential to act as a paracrine factor via the CSF circulation in regulating functions of other brain structures, such as the hypothalamus which is known to express Amhr2. Because circulating Amh produced by the gonads does not cross the blood-brain barrier, 14 the CSF Amh is predominantly generated locally in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Therefore, hippocampal Amh has the potential to act as a paracrine factor via the CSF circulation in regulating functions of other brain structures, such as the hypothalamus which is known to express Amhr2. Because circulating Amh produced by the gonads does not cross the blood-brain barrier, 14 the CSF Amh is predominantly generated locally in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is possible that there was retrograde flow of tracer along the cannula track into the subarachnoid CSF, suggesting that periarterial tracer was due to glymphatic CSF influx rather than ISF efflux. Finally, as shown in a recent study by Bedussi and colleagues, the appearance of tracer in a periarterial distribution may result from pressure injection of tracer into brain tissue immediately adjacent to an artery, rather than occurring as a consequence of true ISF bulk flow (31). Based on these findings, however, it was postulated that once within the arterial wall, parenchymal solutes travel in a direction opposite to blood flow toward larger and more proximal vessels until they ultimately reach the internal cerebral artery (ICA), where solute can be drained by deep cervical lymph nodes (dcLNs) (30,32,33).…”
Section: Anatomy Of Lymphatic Vessels In the Dura Matermentioning
confidence: 99%
“…Several studies showed endothelial dysfunction in cerebral vessels of hypertensive animals (Baumbach & Heistad, ), which might affect the integrity of the BBB. We speculated that this could lead to increased ISF formation, a notion that was supported by increased spreading of tracers released into the hippocampus (Bedussi, Naessens, et al, ). However, more recent work from our group showed that the BBB and blood–CSF barrier function of spontaneously hypertensive rats is still intact with respect to the permeability to small solutes, such as fluorescein (Naessens et al., ).…”
Section: Effects Of Hypertensionmentioning
confidence: 90%
“…Several studies showed endothelial dysfunction in cerebral vessels of hypertensive animals (Baumbach & Heistad, 1988), which might affect the integrity of the BBB. We speculated that this could lead to increased ISF formation, a notion that was supported by increased spreading of tracers released into the hippocampus (Bedussi, Naessens, et al, 2017).…”
Section: Effects Of Hypertensionmentioning
confidence: 97%
See 1 more Smart Citation